2003
DOI: 10.1007/s00211-003-0456-y
|View full text |Cite
|
Sign up to set email alerts
|

A finite element approximation of the Griffith?s model in fracture mechanics

Abstract: The Griffith model for the mechanics of fractures in brittle materials is consider in the weak formulation of SBD spaces. We suggest an approximation, in the sense of − convergence, by a sequence of discrete functionals defined on finite elements spaces over structured and adaptive triangulations. The quasi-static evolution for boundary value problems is also taken into account and some numerical results are shown. (2000): 65N30 Mathematics Subject Classification

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 17 publications
2
56
0
Order By: Relevance
“…Such a scheme does not easily accommodate cohesive finite element methods or discontinuous Galerkin methods. Note that this is partially addressed by a careful estimate of the anisotropy induced by the mesh in (Negri, 1999), (Negri, 2003) or still through the use of adaptive finite element methods (Bourdin and Chambolle, 2000).…”
Section: Numerics and Griffithmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a scheme does not easily accommodate cohesive finite element methods or discontinuous Galerkin methods. Note that this is partially addressed by a careful estimate of the anisotropy induced by the mesh in (Negri, 1999), (Negri, 2003) or still through the use of adaptive finite element methods (Bourdin and Chambolle, 2000).…”
Section: Numerics and Griffithmentioning
confidence: 99%
“…Indeed, a numerical method that relies solely on (8.14) will lead to evolutions whose total energy E(t) is not an absolutely continuous (or even continuous) function (see Figure 11 in (Negri, 2003) or Figure 3(b) in ). This is incompatible with the convergence of the timediscretized to the time continuous evolution, culminating in Theorem 5.5.…”
Section: The Backtracking Algorithmmentioning
confidence: 99%
“…Otherwise, the element is eroded. They showed that in contrast to many other element erosion approaches [66,67,73,74], the eigenerosion approach converges to Griffith fracture with increasing mesh refinement.…”
Section: Element Erosionmentioning
confidence: 99%
“…Several methods have been proposed, based on discontinuous (see [GP03]) or adaptive (see [BC00,Neg03]) finite elements. The class of methods on which we concentrate here relies on approximating the Francfort-Marigo energy, in the sense of Γ -convergence, by means of elliptic functionals.…”
Section: Approximation By Means Of Elliptic Functionalsmentioning
confidence: 99%